Data Violence in Networked Environments: A Study on User Experience - Hasan Hüseyin Kayış (Yeni Medya)
Contact with others in the network in the communication that takes place in networked environments can carry the element of violence in daily life to these environments. In this case, users may encounter data violence in social media applications, which is a form of violence transferred to networked environments. In this study, data violence encountered by users in social media environments is discussed. Identifying the factors that lead to data violence is important in identifying the problem. This study aims to provide a framework for what can be done in the face of these actions that cause serious harm, along with the factors that cause data violence to occur and continue. The complaints of ordinary users about social media environments on an online complaint platform were collected through document analysis and qualitative content analysis was applied to the data. The findings showed that data violence occurs under different categories, from user to user or from platform to user. Platforms' solutions to data violence are inadequate. In order to prevent data violence caused by the technical infrastructure of the platforms, the need for ethical design and ethical operation of the platforms was emphasized and the duties of the authorities were emphasized.